Attention in the Predictive Processing Framework and the Phenomenology of Zen Meditation. - Velasco, Pablo Fernández (Journal of Consciousness Studies, 2017)
In this paper I will use the phenomenology of Zen meditation (zazen) to look at the role of attention within the predictive processing (PP) framework. Section 1 introduces PP, according to which the brain is a dynamical, hierarchical, hypothesis-testing mechanism. Section 2 discusses the current proposal that attention is the process of precision optimization (Hohwy, 2012) and presents some of the challenges for this theory. Section 3 introduces zazen and uses some of the emerging patterns of its phenomenology to clarify the workings of attention, with a special emphasis on the difficulty of maintaining a relaxed and homogeneous state of attention. I claim that this difficulty corresponds to a hyperprior that leads to the expectation of a given level of uncertainty in the world, which in turn pulls attention towards distracting input. Section 4 looks at research about cognitive control and meditation, and concludes that the agent can attempt to impose a global strategy (such as a globally distributed precision expectation) that can affect the assignment of precision expectations, but that this assignment ultimately depends on a complex interplay of different factors. Section 5 discusses some possible challenges for the claims of this paper and Section 6 is a conclusion followed by possible future directions.